TESTING THE EFFECT OF PROCUREMENT ALIGNMENT ON SUPPLY CHAIN PERFORMANCE - Razan Jamlallail; Ahmed Attia (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
One of the key elements for improving the supply chain performance is to ensure achieving the procurement alignment. The main objective of this study is to identify how the procurement practices affect the supply chain performance in terms of performance overtime and competitive performance through measure the procurement alignment within specific dimensions (strategy, process, control, organization, information, and IT) and test the effect of procurement alignment on supply chain competitive and overtime performances. This study used quantitative method based on questionnaire survey to gather the data. The sample is 43 from a population of 250 employees in Petromin Corporation. The statistical analysis from SPSS software showed that there is a significant positive correlation between all eight variables, between procurement within its six dimensions and within supply chain performance two measures. However, the regression analysis showed that the independent variables effect on the supply chain performance measures is not significant enough. To summarize, the results showed that there is a positive relationship between all the mentioned variables but there is no strong effect of them on the performance as a result the hypotheses are partially rejected.